The comprehending teacher: scaffolding in content and language integrated learning (CLIL) - Mahan, Karina Rose (Language learning journal, 2022)
Teaching through a second language (L2) poses many challenges, as second language learners (SLLs) have fewer linguistic resources in the language of instruction. Scaffolding students' learning is a possible way of overcoming these challenges, but there are few studies on this in Content and Language Integrated Learning (CLIL) contexts. The present study suggests a framework for how to empirically identify and classify scaffolding. Using the framework, the study investigates how three Norwegian CLIL teachers support learning for second language learners (SLL) through scaffolding. Twelve lessons (science, geography and social science) were filmed in one 11th-grade CLIL class. A coding manual (PLATO) was used to identify the scaffolding strategies the teachers used. The findings indicate that CLIL teachers scaffold their students to comprehend material. However, they provide few strategies to help students solve tasks, such as modelling and strategy use. CLIL teachers scaffold differently in the natural and social sciences; the natural science teaching has more visual aids, whereas the social science teachers allows for more student talk. The results imply that natural and social science teacher complement each other. However, CLIL teachers need to create more specific learning activities to provide their students with more support.